2020
DOI: 10.1371/journal.pone.0241130
|View full text |Cite|
|
Sign up to set email alerts
|

Plant-growth-promoting Bacillus and Paenibacillus species improve the nutritional status of Triticum aestivum L.

Abstract: Wheat is one of the best-domesticated cereal crops and one of the vital sources of nutrition for humans. An investigation was undertaken to reveal the potential of novel bio-inoculants enriching micronutrients in shoot and grains of wheat crop to eliminate the hazards of malnutrition. Sole as well as consortia inoculation of bio-inoculants significantly enhanced mineral nutrients including zinc (Zn) and iron (Fe) concentrations in shoot and grains of wheat. Various treatments of bio-inoculants increase Zn and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 23 publications
1
18
0
4
Order By: Relevance
“…Our results are similar to results obtained by Prasad and Babu [30], where compatibility was tested between Azospirillum brasilense and Pseudomonas fluorescens for the plant growth promotion of groundnuts. Several studies reported the use of the consortia of various bacterial mixtures for plant growth promotion, nutrient enhancement, abiotic stress management, and biocontrol activities [35,[55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to results obtained by Prasad and Babu [30], where compatibility was tested between Azospirillum brasilense and Pseudomonas fluorescens for the plant growth promotion of groundnuts. Several studies reported the use of the consortia of various bacterial mixtures for plant growth promotion, nutrient enhancement, abiotic stress management, and biocontrol activities [35,[55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Most of these isolates were classified as Bacillus , Paenibacillus , Pseudomonas , Enterobacter , and Sphingomonas spp., all of which are well-known PGPR with beneficial effects on wheat growth and health under controlled and field conditions ( 44 46 ). However, these isolates were tested only on the original Pikovskaya medium ( 31 ), which may not be an appropriate diagnostic indicator of phosphate solubilization activity ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, inoculation with Bacillus aryabhattai impressively improved the nutritional status of wheat crops [22]. The growth and productivity of rice were positively enhanced through treatment with B. aryabhattai.…”
Section: Introductionmentioning
confidence: 99%